Tales from a not-so-posh paris adventure eaudiobook - Russell, Rachel Renée (Dork Diaries, 2023)
Nikki Maxwell deals with the trials and triumphs of middle school in this fifteenth installment of the #1 New York Times bestselling Dork Diaries series! Ooh la la! Nikki Maxwell and her band are on their way to Paris, but they run into some roadblocks on the way... And Nikki's French skills may not be as reliable as she hoped! Can she get them moving again in time to reach their destination?